Analysis Of Employee Recruitment And Placement Policy On Achievement Working At Pt. Langkat Award Prosperous - Pemi Hanifah (Institute of Computer Science (IOCS), 2022)
PT. Anugerah Langkat Makmur is one of the private companies engaged in the planting and processing of palm oil fruits located in the Langkat regency of North Sumatra. Problems in this research is the influence of employment recruitment policy and employee placement simultaneously To Work Achievement At PT. An award of Langkat Makmur. Based on the results of research For simultaneous test obtained that job recruitment and placement of employees simultaneously positive and significant effect on Work Achievement means Hypothesis (H2) previously received.